Transmembrane Peptides as Sensors of the Membrane Physical State - Piotto, Stefano; Di Biasi, Luigi; Sessa, Lucia; Concilio, Simona (Frontiers in Physics, 2018)
Cell membranes are commonly considered fundamental structures having multiple roles such as confinement, storage of lipids, sustain and control of membrane proteins. In spite of their importance, many aspects remain unclear. The number of lipid types is orders of magnitude larger than the number of amino acids, and this compositional complexity is not clearly embedded in any membrane model. A diffused hypothesis is that the large lipid palette permits to recruit and organize specific proteins controlling the formation of specialized lipid domains and the lateral pressure profile of the bilayer. Unfortunately, a satisfactory knowledge of lipid abundance remains utopian because of the technical difficulties in isolating definite membrane regions. More importantly, a theoretical framework where to fit the lipidomic data is still missing. In this work, we wish to utilize the amino acid sequence and frequency of the membrane proteins as bioinformatics sensors of cell bilayers. The use of an alignment-free method to find a correlation between the sequences of transmembrane portion of membrane proteins with the membrane physical state suggested a new approach for the discovery of antimicrobial peptides.